Impacts of Artificial Intelligence on Teachers’ Role in Lalbandi Municipality, Sarlahi, Nepal - Sah, Nawal Kishor (Janajyoti Journal, 2025)
Artificial Intelligence (AI) is the field of computer science which trains machines to imitate intelligent humanabilities such as learning, reasoning, and decision-making. Integration of AI in education has the potential totransform traditional teaching techniques and enhance student achievement, especially in LalbandiMunicipality, Sarlahi District, Madhesh Province, Nepal. The aim of this study is to examine the potentialeffects of AI on the roles, responsibilities, and professional development of educators in this field. The studydetermines the levels of concern, confidence, attitudes, and perceived usefulness towards AI among educatorsby combining a comprehensive literature analysis with primary research including 70 teachers from communityand private school. The results show that there is a lot of ambiguity regarding the ways in which AI may impactdecision-making, job security, and trustworthiness of AI training and its advantages. To address these issues,researcher suggests to improve teachers' self-assurance and comprehension of AI, and cultivate a more positiveattitude toward AI technologies. The study emphasizes the critical need for focused AI training and supportprograms. These findings are essential for creating a context-specific strategy for integrating AI into educationthat puts teachers' needs and agency first, with the ultimate goal of improving Nepal's educational system.